Overcoming the Shock of Foreign Cultures through Cross-Cultural Understanding - Mustakim Mustakim; Umiyati Jabri (Universitas Muhammadiyah Enrekang, 2020)
This paper seeks to slightly explore the issue of cross-cultural understanding that might be beneficial for lecturers of the Muhammadiyah University of Enrekang who have won further study scholarships abroad as well as lecturers who are planning to continue their studies abroad. Understanding different cultures are extremely fundamental as a result of the absence of information culture assumes a job in the utilization of improper correspondence language. Elements of contrasts in an individual's way of life can likewise make individuals look prejudiced toward individuals with various societies. As a lecturer who will be assigned to study abroad, it is very important to